PENGARUH PERADABAN ISLAM TERHADAP DUNIA BARAT - Wendi, Novrizal (Tasamuh: Jurnal Studi Islam, 2016)
The expansion of political power, the Islamic Abbasid period also witnessed the development of civilization is marked by the birth of the Islamic intellectuals like, Muslim philosophers, mutakallimin, mufassirin, muhaddisin, historians and other scientists. They have contributed heavily in building a civilization of Islam in the West. The rapid development of it, is considered by experts as the phenomenon of Islamic progress. In connection with that, Harun Nasution uamat Islam divides the history into three periods namely: first, the classical period (650-1250 AD), the second, the middle period is the time of progress (650-1000 AD) and third; Modern era (1800- present). In the medieval Islamic world, so Islam is advanced and modern. Instead what is happen in the Western world at that time, especially in Europe, is still in the dark, and colored by traditional teachings and the dogmatism of the church. Thatâs because church leaders directly involved in handling the elements of statehood, even more authoritarian and impose his opinion. This paper attempts to photograph the progress of the Islamic world in the Western world.